Decreased Emergency Department Use Following Medicaid Expansion: Evidence from Oregon's Health Insurance Experiment. Issue 3 (3rd July 2021) - Fourkan, MD; Keay, Myoung-Jin; Lee, Na Kyeong
ABSTRACT: In this study, we identify the relationship between Medicaid expansion and emergency department use based on the data from Oregon Health Program. Among the relevant studies, Taubman et al. (2014) provide the positive relationship between two objects with a rather limited approach that leads to the under-identification problem. To avoid the problem, we incorporate a copula regression analysis with an additional endogenous variable. As a result, we find that Medicaid expansion leads to a decrease in emergency department use, which is the opposite result of Taubman et al. (2014).